(untitled) (International Journal of Design (INJUDES), 2021)
Violence in animals, especially dogs, is increasing every day. The lack of education and knowledge about loving dogs is also less given to the wider community. For dog owners will understand more about how to interact and treat dogs, but for those who do not have or get used to the existence of dogs it will be very difficult to love dogs. With the rapid development of age and technology, violence against animals, especially dogs, is becoming increasingly visible by uploading to social media for the purpose of having fun. The rise in violence against animals has led the rest of the world to denounce by making laws that ensnare perpetrators. In reality the community itself does not care about this troubling behavior and ignores the current law. Providing education about dogs can be done early so that when growing up the child does not hurt and love the dog. Therefore, this design was created with the aim of providing information to the public on how to interact and love dogs for children. Giving an education to the child can go through a pleasant thing so as not to feel burdened. Educating through an illustration book will make it easier for the child to learn, this can be done when the child will go to sleep, because the information will be absorbed faster and remembered longer when given at night.